A LOST GENERATION: YOUTH, BLADES, AND COVID-19’S IMPACT ON KNIFE CRIME - Eleni , Christina Antoniou; Dimitrios , Panagiotis Kostas (International Journal of Allied Research in Sociology and Anthropology, 2023)
The COVID-19 pandemic has profoundly influenced youth development and social behavior, necessitating critical examination. This study addresses the escalating concern surrounding youth involvement in serious youth violence, particularly knife crime. The pandemic’s impact on adolescents extends beyond physical health, encroaching upon their social, emotional, and mental well-being. Such encounters with trauma during a crucial developmental phase can potentially yield enduring repercussions throughout their lifespan. Consequently, adolescents grapple with the imperative to adapt their social routines in response to the pandemic’s challenges. Historical discourse has frequently deliberated the exposure of adolescents to shifts, crises, and risky circumstances encompassing social, familial, economic, and health stressors, alongside disruptions to customary routines and support systems (Center for Disease Control and Prevention, 2021; Holland Hawks & Morelli et al., 2021).